The effect of season and management practices on soil microbial activities undergoing nitrogen treatments - interpretation from microcosm to field scale - Rannveig Anna Guicharnaud 1972-; Ólafur Arnalds 1954-; Graeme Ian Paton (2010)
The warming of Arctic regions is causing higher winter and spring temperatures, less snow cover and intensifying seasonal patterns, which in turn have led to a longer growing season in colder regions. In Iceland the climate has become warmer and wetter with lengthening of the growing season and a corresponding increase in arable production. The aim of this study was to assess the effect of seasons and management practices on soil microbial biomass, nitrification, enzymatic activities and labile C availability. A parallel soil microcosms study was conducted to identify the key drivers in a controlled environment. Seasons had a more pronounced effect on soil microbial attributes (dehydrogenase activity, soil microbial biomass and labile C) than soil management with microbial attributes being greater in warmer summer months. This was an indication that continuing climate change and corresponding increase in dehydrogenase activity and soil microbial biomass in soils may increase carbon decomposition and hence loss of organic carbon from cultivated soils in Iceland. Management had a greater impact on soil N dynamics than seasons. There was evidence that precipitation promoted immobilisation of NO3 - -N in soils suggesting that the wetter climate developing in Iceland might reduce the availability of NO3 - -N to crops. Labile C was a governing factor in soil microbial activity as was demonstrated both in the field and the laboratory. Loftlagsbreytingar á norðurhveli jarðar hafa aukið hitastig bæði yfir vetrar og sumarmánuði, skerpt skil milli árstíða, minnkað snjóhulu, og þar með aukið landnýtingarmöguleika á norðlægum slóðum. Svipaðar breytingar hafa verið að þróast hér á landi þar sem hita- og rakastig í andrúmslofti hefur hækkað og lengt vaxtatímabilið auk þess sem hlutdeild ræktarlands stækkar. Megin markmið þessarar rannsóknar var að rannsaka áhrif árstíða og landnýtingar á jarðvegslífmassa, umsetningu niturs, virkni ensíma og aðgengilegt, auðbrjótanlegt lífrænt kolefni í jarðvegi en allir þessir þættir gegna ...